Analysis of Performance Dependencies in NUCA-Based CMP Systems - Foglia, Pierfrancesco; Panicucci, Francesco; Prete, Cosimo Antonio; Solinas, Marco (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2009)
Improvements in semiconductor nanotechnology have continuously provided a crescent number of faster and smaller per-chip transistors. Consequent classical techniques for boosting performance, such as the increase of clock frequency and the amount of work performed at each clock cycle, can no longer deliver to significant improvement due to energy constrains and wire delay effects. As a consequence, designers interests have shifted toward the implementation of systems with multiple cores per chip (Chip Multiprocessors, CMP). CMP systems typically adopt a large last-level-cache (LLC) shared among all cores, and private L1 caches. As the miss resolution time for private caches depends on the response time of the LLC, which is wire-delay dominated, performance are affected by wire delay. NUCA caches have been proposed for single and multi core systems as a mechanism for such tolerating wire-delay effects on the overall performance. In this paper, we introduce our design for S-NUCA and D-NUCA cache memory systems, and we present an analysis of an 8-cpu CMP system with two levels of cache, in which the L1s are private, while the L2 is a NUCA shared among all cores. We considered two different system topologies (the first with the eight cpus connected to the NUCA at the same side -8p-, the second with half of the cpus on one side and the others at the opposite side -4+4p), and for all the configurations we evaluate the effectiveness of both the static and dynamic policies that have been proposed. Our results show that adopting a D-NUCA scheme with the 8p configuration is the best performing solution among all the considered configurations, and that for the 4+4p configuration the D-NUCA outperforms the S-NUCA in most of the cases. We highlight that performance are tied to both mapping strategy variations (Static and Dynamic) and topology changes. We also observe that bandwidth occupancy depends on both the NUCA policy and topology.